Macushla - Rowe, Josephine V. (Lyricist); Macmurrough, Dermot, 1872-1943 (Composer) (Sims Song Slide Corporation (Kirksville, Mo.), 1910)
Songs; Scores; Glass lantern slide depicting score of "Macushla."